Experimental encounters in music and beyond - Coessens, Kathleen (Orpheus Institute series., 2017)
"Experimental encounters in music and beyond opens a necessary dialogue on experimental practices in the arts and negotiates their place in contemporary society. Going beyond the music-historical usage of the term "experimental", this book reimagines experimentation as an open working definition encompassing multiple forms of artistic attitudes and processes. The texts, images, and sounds offer multiple traces, faces, and spaces, revealing what experimentalism in music and the wider arts entails today. With perspectives from a range of disciplines - from choreography through composition to philosophy and beyond - the different experiences and artistic projects documented and discussed explore the complexity of experimentation in a way that is all the richer for being never-ending."--Page 4 of cover